Fractional Cointegration and Futures Hedging - TSE, Yiu Kuen (Institutional Knowledge at Singapore Management University, 1999)
This article examines the performance of various hedge ratios estimated from different econometric models: The FIEC model is introduced as a new model for estimating the hedge ratio. The analysis identifies the prevalence of a fractional cointegration relationship. The effects of incorporating such a relationship into futures hedging are investigated, as is the relative performance of various models with respect to different hedge horizons. Findings include: 1. Incorporation of conditional heteroskedasticity improves hedging performance. 2. The hedge ratio of the EC model is consistently larger than that of the FIEC model, with the EC providing better post-sample hedging performance in the return-risk context. 3. The EC hedging strategy incorporating conditional heteroskedasticity is the dominant strategy. 4. Incorporating the fractional cointegration relationship does not improve the hedging performance over the EC model. 5. The conventional regression method provides the worst hedging outcomes for hedge horizons of 5 days or more.